Two different antibiotic protocols as adjuncts to one-stage full-mouth ultrasonic debridement to treat generalized aggressive periodontitis: A pilot randomized controlled clinical trial - Araujo, Cássia F [UNESP] (2019)
BACKGROUND: To assess the clinical and microbiological responses of amoxicillin + metronidazole (AMX + MET) versus clarithromycin (CLM) as adjuncts to one-stage full-mouth ultrasonic debridement (FMUD) in the treatment of generalized aggressive periodontitis (GAgP). METHODS: For this parallel, double-masked, pilot randomized clinical trial, 46 patients with GAgP were selected and randomly assigned into two groups: AMX+MET group (n = 23): FMUD associated with AMX (500 mg three times a day) and MET (400 mg three times a day) for 7 days; and CLM group (n = 23): FMUD associated with CLM (500 mg twice a day) for 7 days. Clinical parameters were evaluated at baseline, 3, and 6 months post-treatment. The levels of Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Tannerella forsythia, and Fusobacterium nucleatum from subgingival biofilm were determined by quantitative polymerase chain reaction. RESULTS: Both treatments significantly improved all clinical parameters compared with baseline and promoted a significant reduction of A. actinomycetemcomitans and P. gingivalis counts (P > 0.05). CLM succeeded in decreasing T. forsythia at 6 months (P < 0.05), but no antibiotic was able to reduce F. nucleatum. There was no difference between the two protocols regarding the reported adverse effects (P > 0.05). CONCLUSIONS: The results suggest that CLM is not superior than AMX + MET in the treatment of GAgP. However, this antibiotic led to good clinical outcomes and may be a possible alternative to AMX+MET in the treatment of severe periodontitis in young patients. Future studies with larger sample sizes are needed to confirm this statement (NCT02969928).